Mapping of the Snuffbox and Cubital Vessels for Percutaneous Arterial Venous Fistula (pAVF) in Dialysis Patients. Issue 3 (July 2013) - Hull, Jeffrey E.; Kinsey, Emily N.; Bishop, Wendy L.
Purpose: Report on the anatomic qualification of the snuffbox radial artery (SBRA) and proximal radial artery (PRA) for pAVF. Methods: Retrospective analysis of upper extremity mapping in 64 limbs in 55 dialysis patients was performed. The radial artery was assessed for diameter, patency, flow and proximity to the adjacent vein to SBRA and PRA. Sites qualified for pAVF on a binary basis when the in situ radial artery and adjacent vein were straight, parallel, greater than 2 mm in diameter and within 1.5 mm of each other. Effect of age, sex, diabetes, systolic blood pressure and obesity were assessed with logistic regression. Mean, median and frequency distribution of vessel diameter and distance were analyzed. Results: Radial artery sites were qualified for pAVF in 47.6% (30/63) at the SBRA and 87.9% (29/33) at the PRA. SBRA sites were disqualified for vessel size in 36.4% (12/33 overall, usually vein 11/12), distance in 24% (8/33) and both 36.4% (12/33). All (4/4) PRA sites were disqualified for vessel size alone. The adjacent vein was the median vein or cephalic vein for the SBRA, and the perforating vein or vena comitans for the PRA. Effects of age, sex, diabetes, systolic blood pressure, obesity and prior fistula did not attain statistical significance. Conclusions: Most dialysis patients meet the anatomic requirements for pAVF in the SBRA or PRA. Vessel size is the most common limiting variable followed by distance between vessels.